Chronic Psychological Stress Accelerates Vascular Senescence and Impairs Ischemia‐Induced Neovascularization: The Role of Dipeptidyl Peptidase‐4/Glucagon‐Like Peptide‐1‐Adiponectin Axis. Issue 10 (28th September 2017) - Piao, Limei; Zhao, Guangxian; Zhu, Enbo; Inoue, Aiko; Shibata, Rei; Lei, Yanna; Hu, Lina; Yu, Chenglin; Yang, Guang; Wu, Hongxian; Xu, Wenhu; Okumura, Kenji; et al.
Abstract : Background: Exposure to psychosocial stress is a risk factor for cardiovascular disease, including vascular aging and regeneration. Given that dipeptidyl peptidase‐4 (DPP4) regulates several intracellular signaling pathways associated with the glucagon‐like peptide‐1 (GLP‐1) metabolism, we investigated the role of DPP4/GLP‐1 axis in vascular senescence and ischemia‐induced neovascularization in mice under chronic stress, with a special focus on adiponectin ‐mediated peroxisome proliferator activated receptor‐γ/its co‐activator 1α (PGC‐1α) activation. Methods and Results: Seven‐week‐old mice subjected to restraint stress for 4 weeks underwent ischemic surgery and were kept under immobilization stress conditions. Mice that underwent ischemic surgery alone served as controls. We demonstrated that stress impaired the recovery of the ischemic/normal blood‐flow ratio throughout the follow‐up period and capillary formation. On postoperative day 4, stressed mice showed the following: increased levels of plasma and ischemic muscle DPP4 and decreased levels of GLP‐1 and adiponectin in plasma and phospho‐AMP‐activated protein kinase α (p‐AMPKα), vascular endothelial growth factor, peroxisome proliferator activated receptor‐γ, PGC‐1α, and Sirt1 proteins and insulin receptor 1 and glucose transporter 4 genes in the ischemic tissues, vessels, and/or adipose tissues and numbers of circulating endothelial CD31 + /c‐Kit + progenitor cells. Chronic stress accelerated aortic senescence and impaired aortic endothelial sprouting. DPP4 inhibition and GLP‐1 receptor activation improved these changes; these benefits were abrogated by adiponectin blocking and genetic depletion. Conclusions: These results indicate that the DPP4/GLP‐1‐adiponectin axis is a novel therapeutic target for the treatment of vascular aging and cardiovascular disease under chronic stress conditions.